The character of mind : an introduction to the philosophy of mind - McGinn, Colin (Oxford University Press, 1996)
Of what nature is the mind? So Colin McGinn starts his first chapter, and this is his guiding question. He pursues the answer with a boldness and provocativeness rarely encountered in philosophical writing. As he explains, my aim has been to give the reader something definite and stimulating to think about, rather than to present a cautious and disinterested survey of the state of the subject.